Entre a “loucura” e a “normalidade”: proposição de um material didático referente a história do hospital colônia de Barbacena e as discussões atuais a respeito da diversidade - Gomes, Karolliny Nardino (2017)
Issues related to human diversity have been subject of much discussion and dialogue in recent times. Gender, culture, ethnicity, religious diversity are some of the themes focused and debated both in the social and educational environment. And one way to make this thematic more contextual in the school, is include Science History, since it allows to approach the student scientific knowledge understanding besides being a facilitating and interesting way of learning. Thus, the present work presents a discussion that culminated in didactic support material on human diversity issues, madness and normality, bringing the historical Hospital Colônia de Barbacena - Minas Gerais case, articulated with Science History contributions through the eugenics movement. This study objetive was analyze Hospital Colônia de Barbacena historical period through a bibliographical review to understand the biological and ideological discourses that underpinned actions that occurred in this institution and, thus, construct and validate among peers a didactic proposal on science dealing nature with Hospital Colônia de Barbacena case, discussions about human diversity and role of scientific discourse in society. The research methodology employed was carried out in two moments: one is dedicated to analyze documents from public sources about Hospital Colônia de Barbacena - MG and related to eugenics movement and the other is focus on pairs validation and analysis of didactic support material constructed. In addition, data was interpreted according to Bardin perspective (2006). The validation, sought to investigate the limits and possibilities that didactic material can contribute to address human diversity theme in the school. The support material validation was carried out for six participants from to the initial formation, public network education professors, masters and doctorate. The results included analysis of the pairs and authors reflection about material application. The pairs showed that didactic material is an excellent tool to discuss issues related to diversity, contributing and enriching the learning about scientific knowledge, enabling student to learn in a critical and reflective way. Still, it made possible an experience and reflection exchange place approach the daily science being a thematic relevant for the education. As limits, development time lack question was evidenced; the little approach on the legislation for diversity and the eugenic movement. As an authors reflection in addition to the issues cited by the peers, it was evidenced material dynamics lack. Thus, a restructured sequence is suggested at the end of results analysis, which took into account the validation notes and the authors' reflections. Finally, we believe Science History discussions combination about and human diversity theme allows a greater understanding and learning about scientific knowledge and human society, since it allows to create greater relations and understand different faces of science and diversity respect in general.